Selling french sex: prostitution, trafficking, and global migrations - Camiscioli, Elisa (Cambridge University Press, 2024)
"Selling French Sex challenges contemporary understandings of trafficking by exploring the discourses and experiences surrounding the migration of French women for work in the early-twentieth-century sex industry. It will interest students and scholars of French, immigration, women's and gender, and world history"-- Provided by publisher